Dye-decolourizing yeasts isolated from Las Yungas rainforest. Dye assimilation and removal used as selection criteria - Martorell, María Martha (2012)
Thirty-nine yeast isolates from " Laurel del Monte" underlying soil from " Las Yungas" rainforest (Tucumán, Argentina) were obtained following an isolation scheme on both, dye tolerance and assimilation. Fifteen isolates were selected based on their ability to decolourize agar plates containing four industrial textile dyes, either alone or as a mixture. Eight isolates were further selected according to their assimilation of dyes as sole Carbon/energy or Nitrogen source. Selected yeasts belonged to the basidiomycetous genus Trichosporon and the ascomycetous genera Cyberlindnera, Barnettozyma and Candida. Decolourization, biomass production and enzymatic production of manganese peroxidase, laccase and tyrosinase were then studied in liquid media. Isolate Candida sp MM 4035 was selected for future experiments and further molecular characterization and physiological tests are in progress in order to achieve the potential description of a new ascomycetous yeast.